2018
DOI: 10.1038/s41419-018-1152-2
|View full text |Cite
|
Sign up to set email alerts
|

PINK1/Parkin-mediated mitophagy is activated in cisplatin nephrotoxicity to protect against kidney injury

Abstract: Cisplatin is a widely used chemotherapeutic drug with notorious toxicity in the kidneys, which involves mitochondrial dysfunction and damage in renal tubular cells. Mitophagy is a form of selective autophagy that removes damaged or dysfunctional mitochondria to maintain cellular homeostasis. In this study, we have used mouse and cell models to examine the role and regulation of mitophagy in cisplatin nephrotoxicity. Cisplatin treatment was associated with the activation of autophagy and mitophagy. Rapamycin, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
97
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(107 citation statements)
references
References 50 publications
(51 reference statements)
8
97
2
Order By: Relevance
“…Mitophagy is found to be induced during acute kidney injury (14,22,37,38) and compromised during CKD in animal models (39,40). Mitochondrial dysfunction is also reported in human kidney disease (33).…”
Section: Discussionmentioning
confidence: 98%
“…Mitophagy is found to be induced during acute kidney injury (14,22,37,38) and compromised during CKD in animal models (39,40). Mitochondrial dysfunction is also reported in human kidney disease (33).…”
Section: Discussionmentioning
confidence: 98%
“…Some studies have shown that P53 can interact with Parkin's RING0 region 30,31 . The PINK1-Parkin pathway is the most important pathway by which mitophagy is mediated 42 ; therefore, to further study whether P53 regulated mitophagy via this pathway, we continued to treat BMSCs for 24 h using an H 2 O 2 (1000 μM)-simulated OS. − Parkin groups.…”
Section: Mechanism Of P53 Regulating Mitophagymentioning
confidence: 99%
“…The loss of the park protein is a cause of great cellular stress as a major mitophagy mechanism is compromised to potentially result in the accumulation of non-functional mitochondria. Under normal circumstances, the park ubiquitin ligase recruits the Drp1 protein to mediate mitochondrial fragmentation during mitophagy [20,49]. In mouse embryonic broblasts, loss of park does not have any effect upon the number of mitochondria [50].…”
Section: Discussionmentioning
confidence: 99%